2019
DOI: 10.3390/educsci9010038
|View full text |Cite
|
Sign up to set email alerts
|

Texas–Mexico Border vs. Non-Border School Districts’ Growth Trajectory of High-Stakes Reading Performance: A Multi-Level Approach

Abstract: This study focuses on comparing the growth trajectory of border and non-border school districts regarding their fifth-grade students’ performance on a standardized reading test. Using a growth hierarchical linear model, we investigated the effect of time, school location, and their interaction on students’ reading performance through the State of Texas Assessment of Academic Readiness (STAAR) reading test in five recent school years. It was found that border school students lagged behind in reading at the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The primary reason for the low achievement in Border districts is the large concentration of disadvantage along the Border in Texas (Garcia et al 2022). This result is consistent with previous research, which found that students attending school districts along the Texas-Mexico Border underperformed compared with their non-Border peers (Tang, Wang, and Min 2019). In addition to finding contrasting findings, this study differs from the previous studies in that it compares Latinx and White achievement (i.e., test score disparities).…”
Section: Latinx Academic Achievementsupporting
confidence: 93%
“…The primary reason for the low achievement in Border districts is the large concentration of disadvantage along the Border in Texas (Garcia et al 2022). This result is consistent with previous research, which found that students attending school districts along the Texas-Mexico Border underperformed compared with their non-Border peers (Tang, Wang, and Min 2019). In addition to finding contrasting findings, this study differs from the previous studies in that it compares Latinx and White achievement (i.e., test score disparities).…”
Section: Latinx Academic Achievementsupporting
confidence: 93%
“…Geographic isolation creates the space for hands-on student exploration of the natural world. Furthermore, due to limited district resources, we recommend the use of structured online professional development with a focus on improving teachers' scientific knowledge and place-based pedagogy (Tang et al 2019). We urge teachers and schools to partner with researchers to develop research-based curriculum and resources that reflect the local community and knowledge to serve the diverse needs of rural students.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation considered data at the elementary school level, where it is expected that ELL students are in the process of developing the skills required to perform using their second language at an academic level (Abedi & Levine, 2013;Lakin & Young, 2013). Recent research results support these assertions where differences on performance on standardized assessment were reported considering English Language Learners children from school districts located at the Texas border with Mexico compared with non-border school districts (Tang, Wang & Min 2019;Vela, Jones, Mundy & Isaacson, 2017). The Hispanic population is growing faster than other minority student population in Texas.…”
Section: Discussionmentioning
confidence: 99%